Human Immunodeficiency Virus–2 (HIV-2): A Summary of the Present Standard of Care and Treatment Options for Individuals Living with HIV-2 in Western Europe. (30th March 2020) - Berzow, Dirk; Descamps, Diane; Obermeier, Martin; Charpentier, Charlotte; Kaiser, Rolf; Guertler, Lutz; Eberle, Josef; Wensing, Annemarie; Sierra, Saleta; Ruelle, Jean; Gomes, Perpetua; Mansinho, Kamal; et al.
Abstract: Human immunodeficiency virus–2 (HIV-2) is endemic in some countries in West Africa. Due to the lower prevalence in industrialized countries, there is limited experience and knowledge on the management of individuals living with HIV-2 in Europe. Compared to HIV-1, there are differential characteristics of HIV-2 regarding diagnostic procedures, the clinical course, and, most importantly, antiretroviral therapy. We integrated the published literature on HIV-2 (studies and reports on epidemiology, diagnostics, the clinical course, and treatment), as well as expert experience in diagnosing and clinical care, to provide recommendations for a present standard of medical care of those living with HIV-2 in Western European countries, including an overview of strategies for diagnosis, monitoring, and treatment, with suggestions for effective drug combinations for first- and second-line treatments, post-exposure prophylaxis, and the prevention of mother-to-child transmission, as well as listings of mutations related to HIV-2 drug resistance and C-C motif chemokine receptor type 5 and C-X-C motif chemokine receptor type 4 coreceptor tropism. Abstract : Human immunodeficiency virus–2 (HIV-2) is different from HIV-1 in diagnosis, clinical course, and antiretroviral treatment. Due to the poor data situation, we present considerations for reliable HIV-2 testing, monitoring, and treatment strategies based on available knowledge and expert opinions.